THE EFFECTIVENESS OF THINK PAIR SHARE WITH SERIES PICTURES AS MEDIA TO IMPROVE THE STUDENTS’ SPEAKING ABILIT; A CASE OF THE ELEVENTH GRADE STUDENTS OF SMA N 14 SEMARANG - Muhammad Abied Fauzi Jr (Universitas PGRI Semarang, 2013)
The objectives of the study are (1) To find out the speaking ability of SMA Negeri 14 Semaran students before being taught using think pair share with series pictures.(2)To find out the speaking ability of SMA Negeri 14 Semarang students after being taught using think pair share with series pictures.(3)To find out whether or not there is a significant difference of speaking ability of SMA Negeri 14 Semarang students before and after being taught using think pair share with series pictures . In this study the writer chooses experimental method. The writer chooses one class as the subject. The class consists of 30 students. The writer uses a test as instrument. Then the writer also gives the treatment to improving student’s speaking ability by using think pair share with series picture. Compared to using this technique, improving student’s speaking ability by using think pair share with series pictures has given better result as indicated by the significant statistical t-test computation that the t-obtained is higher than t-table. The t-obtained is 9,71 and t-table in the level of significant is 2,04. So, the t-obtained is higher than t-table that is 9,71> 2,04. The mean of the class before treatment is 61,03 and after the treatment, the mean is 76,1. It means that using think pair share with series pictures is effective in improving student’s speaking ability. From the data analyzed, it is concluded that improving student’s speaking ability by using think pair share with series pictures is much better than without using them. The students comprehend to speak is improved significantly. Thus, Think pair share with series pictures is the effective method to be used in teaching English for eleventh year students of SMA N 14 Semarang. Finally, based on the findings, it is suggested that to improve student’s speaking ability by using think pair share with series pictures at the Eleventh year students of SMA N 14 Semarang is a good technique. The English teacher should be creative to choose the technique in improving student’s speaking ability by using think pair share with series pictures that is appropriate with the material and students condition. A good and interesting technique will motivate and stimulate the students to be interested in learning English.